Isolation, Identification, and Antimicrobial Study of Yersinia spp. Isolated from Traditional and Industrial Olivier Salad Specimens in Tehran - Farnaz Eskandarzadeh; Mohammad Reza Mohammadi; Abbas Rahimi Foroushani; Mohammad Mehdi Soltan Dallal (Journal of Nutrition and Food Security)
Background: Yersinia enterocolitica is a gram-negative bacteria and one of the most important food-borne bacteria that causes yersiniosis. Several studies have investigated various species of this gastrointestinal pathogen in food and water sources. Although Olivier salad is a ready-to-eat and easily available cold food, it is highly susceptible to microbial contaminations. This study aims to investigate the presence of Yersinia spp., especially the pathogenic Yersinia enterocolitica in Olivier salad. Methods: In this cross-sectional descriptive study, 150 specimens (traditional and industrial Olivier salad) were collected and tested for the presence of Yersinia spp. Using the Iranian National Standard No. 4556. Obtained data were analyzed statistically using descriptive statistics in IBM SPSS. Results: Yersinia spp. contamination was found in only 6% of traditional specimens (6 out of 100). Based on biochemical reactions, four isolates of Yersinia enterocolitica and two isolates of Yersinia intermedia were identified from six Yersinia isolates. The biotype of Yersinia enterocolitica was investigated, and three strains of biotype 1A and one strain of biotype 1B were identified. The human pathogenic serotype was not found in the serotype analysis. Conclusion: The study results showed that specimens of traditionally prepared Olivier salad were contaminated with Yersinia spp. Yersinia enterocolitica is the most prevalent species as expected, and the analysis of the strains of this species revealed that it also contains other biotypes, including the highly pathogenic biotype 1B.